The Epic of Labaw Donggon. [anthology].
Labaw Donggon is one of three handsome sons of the diwata Abyang Alunsina and her moral husband Buyung Paubari, the other two being Humadapnon and Dumalaplap. Being of semi-divine birth, the three possess extraordinary powers. Labaw Donggon, for instance, miraculously grows into a sturdy young man shortly after his birth and embarks upon the first of his three courting adventures.